Studies on Neotropical crickets: Aclodes paz n. sp. a new phalangopsid cricket (Orthoptera: Phalangopsidae) from the Santander caves, Colombia - Cadena-Castañeda, Oscar J.; Quintana-Arias, Ronald Fernando; Rodríguez, Diana Marcela Trujillo; Sarmiento, Juan Pablo Prias; Castellanos-Morales, Cesar A. (Zootaxa, 2022)
Aclodes paz n. sp. a new troglophilous species from the caves of the municipalities of La Paz and San Vicente del Chucurí, Santander, is described. An overview of the taxonomic history of the tribe Aclodini and the genus Aclodes is provided, to understand the recent taxonomic changes in the group. The species is named in honor of La Paz’s municipality and the desire of Colombians and other inhabitants of the world who have conflicts in their territories (the cricket of peace). Finally, the habitat and taxonomy of the genus are discussed.